Slow-release urea in diets for lactating crossbred cows - Santiago,Bruno Tadeu (2015)
The objective of this study was to evaluate the performance of F1 (Holstein × Zebu) cows in lactation according to different levels of substitution of soybean meal for a protein equivalent non-protein nitrogen originated from slow-release urea (SRU). Eight F1 (Holstein × Zebu) cows in the first third of lactation, with an average milk yield of 12.7 kg (±3.1 kg)/day and a live weight of 552 kg (±30 kg), were used. The experimental design was composed of two simultaneous 4 × 4 Latin squares, with the following treatments: 100% soybean meal and 0% SRU; 66% soybean meal and 34% SRU; 34% soybean meal and 66% SRU; and 0% soybean meal and 100% SRU. Sorghum silage, used as roughage, was supplied together with the concentrate. Feed intake and digestibility as well as milk yield and milk composition were measured. The obtained data were subjected to analysis of variance, adopting a 5% probability level. No intake variable showed significant differences among the treatments, and the mean values for the intakes of dry matter (DM), crude protein (CP) and neutral detergent fiber (NDF) were 18.35 2.62 and 5.85 kg/day, respectively. The results for apparent digestibility also did not show differences among treatments, with DM, CP and NDF averaging 58.16, 58.64 and 36.21%, respectively. Milk yield and composition were similar among the treatments. The average 4%-fat-corrected milk yield was 13.39 kg/animal day. Intake, digestibility and milk yield and composition variables are not changed according to the substitution of the soy protein for slow-release urea. Thus, for average-milk-yield crossbred.animals, this substitution depends on economic variables only.